Design of control circuit for an inverter - Nurfaiza Hanim Mohd Saleh
This thesis develops sinusoidal pulse width modulation (SPWM) technique switching for single phase bridge inverter. This technique is design using (VHDL) programming with Altera Quartus II environment. A general framework for switching control is developed, which encompasses relevant Metal Oxide Semiconductor Field Effect Transistor (MOSFET). Theoretically, the switching technique for inverter circuit need to produce output waveform as close as the purely sine wave as generated by the ideal inverter. Therefore, this method is developed with high programming flexibility as to accomplish purely sine wave from the inverter output terminal. Three part circuits of the design are involved software development, interface circuit and the inverter circuit. Simulations are used to further corroborate the results and done prior to the hardware design. Field Programmable Gate Array (FPGA) Technology is adapted as the part of the circuit design in order to control the switching of the inverter switches. The switching frequency of this project is 2.083 khz with the fundamental frequency of 50.25 hz out from the tested inverter.